2012
DOI: 10.1589/jpts.24.821
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low Back Pain in Fast Bowlers a Comparative Study of Core Spinal Stabilization and Conventional Exercises

Abstract: Fast bowlers are very prone to low back pain. Due to persistence of chronic low back pain (cLBP) fast bowlers suffer disturbances in their daily living and sports specific activities that lead to functional disability. The purpose of this study was to investigate the effect of spinal core stabilization exercises on the pain intensity and the functional activity of fast bowlers. [Subjects] Thirty male fast bowlers with cLBP with a mean age of 20.79 ± 2.08 years [Methods] Subjects were screened for this study by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The lumbar muscle is crucial in daily life, allowing the body to maintain various positions; therefore, maintaining enough lumbar muscle strength and stamina is very important. In this regard, it has been reported that lack of co-contraction of the lumbar muscle is strongly related to lumbar instability 13 , 14 , 15 ) . To prevent dysfunction of the trunk muscle, which causes lumbar instability, core strengthening exercises must be practiced 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The lumbar muscle is crucial in daily life, allowing the body to maintain various positions; therefore, maintaining enough lumbar muscle strength and stamina is very important. In this regard, it has been reported that lack of co-contraction of the lumbar muscle is strongly related to lumbar instability 13 , 14 , 15 ) . To prevent dysfunction of the trunk muscle, which causes lumbar instability, core strengthening exercises must be practiced 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…These 2 preventive measures have been widely discussed in earlier studies for sports other than alpine ski racing. 19,21,22,25,32,39 With respect to the second objective, external interventions such as changes in equipment, course settings, or snow preparation strategies might be promising for reducing the magnitude of variables related to spinal disc loading. These interventions have already been suggested to have a certain potential to affect skiers' general kinematics and/ or loading.…”
Section: Potential Prevention Approaches For Overuse Injuries Of the Back In Alpine Ski Racingmentioning
confidence: 99%
“…Core stabilisation exercise (final score 2.4/10) was superior to conventional strengthening exercise (final score 3.3/10) for improving pain in cricket players (p=0.002), 24 although both interventions improved pain. Compared with a basic lumbar extensor strength programme, a dynamic stabilisation training programme resulted in greater improvement in VAS (2.1 times more) and greater rate of improvement of other outcome measures in hockey players.…”
Section: Reviewmentioning
confidence: 93%
“…Core stabilisation exercise (final ODI 19.8±4.9) was superior to conventional strength exercise (final ODI 22.2±5.4) for improving disability in cricket players (p<0.001) with improvement with both exercise types. 24 Resistance exercise (Thera-band) (final ODI 17.2±1.78) was superior to Swiss ball exercise (final ODI 18±0.8) in hockey players (p<0.001), although both types of exercise training resulted in improvements. 30 A periodised resistance training programme was compared by Jackson et al 22 to a group who continued with 'regular recreational activity only' (no resistance training allowed) and resulted in significant improvements in disability in middle-aged athletes.…”
Section: Reviewmentioning
confidence: 94%
See 1 more Smart Citation